Pendampingan dan Penerapan Branding Produk UMKM Sofood Nugget Sayur - Kharisma Mutiara Aisyah; Indah Respati Kusumasari (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Indonesia has unlimited biological wealth and is widely spread throughout the country. Each region in Indonesia has a wide variety of flora and fauna, some of which are food commodities in each region. In its development, regions producing a food commodity will sell it in processed form. The city of Blitar has many MSMEs engaged in the production of typical food and beverages. Such as, traditional food, souvenir products, and others. These MSMEs faces similar obstacles when managing their business. The lack of branding skills in introducing products to consumers is the main reason why MSME actors experience difficulties in building brand awareness.